2003
DOI: 10.1021/ic030171f
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Coordination Chemistry of Oxomolybdenum Organoarsonate Materials

Abstract: The oxomolybdenum-arsonate system was investigated under hydrothermal conditions in the presence of charge-compensating copper(II)-organonitrogen complex cations as secondary building blocks. A series of materials of the Mo/O/As/Cu/ligand family has been prepared and structurally characterized. The architectures of the products reflect the identity of the arsonate component and the organonitrogen ligand, as well as the reaction conditions. The structural versatility of this emerging class of compounds is manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
77
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 36 publications
(33 reference statements)
0
77
1
Order By: Relevance
“…So far the reports on molybdenum arsenates have been mainly concentrated on several discrete molybdenum arsenate clusters [7,8]. Only recently, an interesting systemic study on extended structures based on molybdenum organoarsonate have been performed by Zubieta and his co-workers, and the use of inorganic molybdearsenate clusters as secondary building units (SBUs) to construct extended structures still seldom has been reported [9]. Therefore, further research is necessary to enrich and develop this branch.…”
Section: Introductionmentioning
confidence: 99%
“…So far the reports on molybdenum arsenates have been mainly concentrated on several discrete molybdenum arsenate clusters [7,8]. Only recently, an interesting systemic study on extended structures based on molybdenum organoarsonate have been performed by Zubieta and his co-workers, and the use of inorganic molybdearsenate clusters as secondary building units (SBUs) to construct extended structures still seldom has been reported [9]. Therefore, further research is necessary to enrich and develop this branch.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are important because of their possible application in catalysis, 12,13 gas storage, [14][15][16][17] electrical conductivity, 18 biology, 19,20 and many more areas. Molybdenum oxide based materials are interesting from a structural point of view 21,22 but molybdenum oxide based materials containing alkali metal clusters are rarely reported. Bimetallic compounds containing alkali metal clusters, for example gallium phosphonates, have been synthesized and shown to form cages containing lithium, 1 sodium, and potassium 23 ions with short metal-metal contacts.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In this way, the design and synthesis of new composite materials by incorporating POM and transition/rare-earth metal complex moieties constitute an emerging area of interest. [9][10][11][12][13] In 1971, Peacock and Weakley 14 first put forward that the monovacant Keggin anions [XW 11 O 39 ] n-(X=Si IV , P V ) formed both 1∶1 and 1∶2 compounds with rare earth ions in solution. In 2000, Pope et al 15 reported the structural characterization of the one-dimensional (1D) 1 ∶ 1 [Ln(α-SiW 11 O 39 )(H 2 O) 3 ] 5 -(Ln = La III , Ce III ) compounds, showing that these anions are polymeric in the solid state.…”
Section: Introductionmentioning
confidence: 99%